Reading Palestinian Resistance through Peircean Semiotics: A Semiotic and Qur’anic Analysis of Mahmoud Darwish’s Identity Card - Pratama, Rendi; Masnani, Sitti Wahidah; Mujadilah, Mujadilah; Agussalim, Andi; Ridwan, Muhammad (Jurnal Adabiyah, 2025)
This study aims to analyze the poem Identity Card by Mahmoud Darwish as a representation of the identity and resistance of the Palestinian people through Charles Sanders Peirce’s semiotic approach which includes icons, indexes, and symbols. The focus of the study is directed at how the meaning of suffering, attachment to the land, and the strengthening of collective identity are articulated in the poem, as well as its relationship to the Qur’anic principles of maintaining identity, defending the homeland, and resisting oppression. The research method used is qualitative-descriptive with Peirce’s semiotic approach. Primary data is in the form of the text of the poem Identity Card, while secondary data is obtained from scientific literature on the life of Mahmoud Darwish, the context of the Palestinian struggle, as well as the study of interpretation and hadith related to the value of resistance. An analysis of the nine main quotes of the poem was carried out using the Peirce framework, then enriched with a normative-religious perspective to reveal the ethical and spiritual dimensions of the resistance presented. The results of the study show that the icon depicts the concrete reality of the suffering of the Palestinian people due to occupation; the index reflects an existential attachment to the land understood as a divine trust; Meanwhile, symbols contain collective resistance through diction such as "angry", "name", and Identity Card that affirm pride and courage in the face of oppression. These three aspects are in harmony with the values of the Qur’an: identity as sunnatullah (QS. Al-Ḥujurāt: 13), land as a trust (QS. Nūḥ: 19), and resistance to tyranny as a manifestation of faith (HR. Muslim, no. 49). Thus, the poem Identity Card is not only an aesthetic work, but also a cultural, ideological, and spiritual discourse that represents the collective struggle of the Palestinian people and offers a universal meaning of justice and humanity. ملخص يهدف هذا البحث إلى تحليل قصيدة "بطاقة الهوية" لمحمود درويش كتمثيل لهوية الشعب الفلسطيني ومقاومته من خلال سيميائية تشارلز ساندرز بيرس (الأيقونات، الفهارس، الرموز). ينصب تركيزه على معنى المعاناة والتعلق بالأرض وتعزيز الهوية الجماعية، ويرتبط بالمبادئ القرآنية في الدفاع عن الهوية والدفاع عن الوطن ومحاربة الاضطهاد. يستخدم منهج البحث هذا النوعية الوصفية مع المنهج السيميائي لتشارلز ساندرز بيرس (الأيقونات والفهارس والرموز). البيانات الأولية في شكل نص قصيدة "بطاقة الهوية"، بينما تأتي البيانات الثانوية من الأدبيات العلمية حول الدرويش والنضال الفلسطيني. تم تحليل الاقتباسات الشعرية التسعة من خلال إطار بيرس، وإثرائه بمقاربة معيارية دينية قائمة على القرآن والحديث، بحيث يمكن قراءة معنى المقاومة ليس فقط سياسيا، ولكن أيضا أخلاقيا وروحيا. تظهر النتائج أن الأيقونة تصور الواقع الملموس لحياة الشعب الفلسطيني، والمؤشر يعكس المعاناة والتعلق بالأرض كأمانة، بينما يؤكد الرمز الهوية الجماعية والمقاومة من خلال كلمات مثل "غاضب" مليئة بالمقاومة. تتماشى هذه النتيجة مع القرآن: الهوية كسنة الله (QS. الحجرات: 13) ، الأرض كأمانة (QS. نوح: 19) ، ومقاومة الظلم كجزء من الإيمان (HR. Muslim ، رقم 49). قصيدة محمود درويش "بطاقة الهوية" ليست مجرد تعبير جمالي، بل هي تمثيل للمعاناة الجماعية للشعب الفلسطيني التي تتناغم مع القيم القرآنية للهوية والأرض ومقاومة الاضطهاد. وهكذا ، تعمل هذه القصيدة كتعبير جمالي بالإضافة إلى خطاب ثقافي وأيديولوجي وروحي يؤكد المقاومة ويعطي معنى عالميا للنضال ضد الظلم. Abstrak Penelitian ini bertujuan menganalisis puisi Identity Card karya Mahmoud Darwish sebagai representasi identitas dan perlawanan rakyat Palestina melalui pendekatan semiotika Charles Sanders Peirce yang meliputi ikon, indeks, dan simbol. Fokus kajian diarahkan pada bagaimana makna penderitaan, keterikatan pada tanah, dan penguatan identitas kolektif diartikulasikan dalam puisi tersebut, serta keterkaitannya dengan prinsip-prinsip Al-Qur’an tentang menjaga identitas, membela tanah air, dan melawan penindasan. Metode penelitian yang digunakan adalah kualitatif-deskriptif dengan pendekatan semiotika Peirce. Data primer berupa teks puisi Identity Card, sedangkan data sekunder diperoleh dari literatur ilmiah mengenai kehidupan Mahmoud Darwish, konteks perjuangan Palestina, serta kajian tafsir dan hadis terkait nilai resistensi. Analisis dilakukan terhadap sembilan kutipan utama puisi menggunakan kerangka Peirce, kemudian diperkaya dengan perspektif normatif-religius untuk menyingkap dimensi etis dan spiritual dari perlawanan yang dihadirkan. Hasil penelitian menunjukkan bahwa ikon menggambarkan realitas konkret penderitaan rakyat Palestina akibat penjajahan; indeks merefleksikan keterikatan eksistensial pada tanah yang dipahami sebagai amanah ilahi; sedangkan simbol mengandung perlawanan kolektif melalui diksi seperti “marah”, “nama”, dan “kartu identitas” yang menegaskan kebanggaan dan keberanian menghadapi penindasan. Ketiga aspek tersebut selaras dengan nilai-nilai Al-Qur’an: identitas sebagai sunnatullah (QS. Al-Ḥujurāt: 13), tanah sebagai amanah (QS. Nūḥ: 19), dan perlawanan terhadap kezaliman sebagai manifestasi iman (HR. Muslim, no. 49). Dengan demikian, puisi Identity Card bukan hanya karya estetis, melainkan juga wacana kultural, ideologis, dan spiritual yang merepresentasikan perjuangan kolektif rakyat Palestina serta menawarkan makna universal tentang keadilan dan kemanusiaan.